A comprehensive review of disruptive technologies in disaster risk management of smart cities - Chao Han; Shan Zang (Climate Risk Management)
The integration of disruptive technologies into smart cities may contribute to a more robust disaster response system.. This paper offers a comprehensive overview of disruptive technologies that are currently being used or suggested for future advancements in urban disaster management. These technologies include the Internet of Things (IoT), image processing, artificial intelligence (AI), big data, and smartphone applications. The main objective of this article is to investigate potential models for smart city development that would allow us to make better use of disruptive innovations and enhance disaster recovery efforts. The main points that are covered include (a) how new technologies can be used to improve upon current disaster management techniques and (b) what are the limitations or obstacles to using disruptive methods in this field. This research presents a new integrated framework that uses artificial intelligence (AI) driven big data analytics for disaster forecasting, early warning systems, and recovery after a disaster, as compared to previous studies that have focused on single uses of disruptive technology. In order to make smart cities more resilient to disasters, this study offers a comprehensive approach that combines processing data from several sources, predictive modelling, and efficient allocation of resources. To address these concerns, we offer an innovative approach for creating a disaster management strategy that make use of disruptive technologies and which depends on integrated methods founded in big data analysis and artificial intelligence.